Dampak Broken Home Terhadap Motivasi Belajar Siswa di SDN Campurejo Tretep Temanggung (Studi Fenomenologi pada Anak Broken Home) - Nurnaila, Siti Azza; Munawaroh, Hidayatul (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Along with the increasing divorce rate in Indonesia, this has an impact It cannot be denied that children have many causes decreased children's learning achievement. This research was carried out to find out and describe the influence of a broken home on learning motivation student. This research was carried out at SDN Campurejo Tretep Temanggung to answer the phenomenon of children who are victims of divorce between two people old. This research uses qualitative research. For technique Data collection is observation, interviews and personal documentation with technically listen, record and write. In determining the population, data is obtained randomly primer from the guidance and counselling teacher (BK). Meanwhile, for processing techniques. The author's data uses descriptive techniques. The results of the author's research. What do children with broken homes do have forms of motivation low learning, such as: lazy to go to school; often absent without information; not doing school work; sleeping in class; annoying friends studying time; not listening to the teacher's directions when studying; even disobeying the teacher.